2012
DOI: 10.1136/bmjopen-2012-001689
|View full text |Cite
|
Sign up to set email alerts
|

Ankle-Brachial Index determination and peripheral arterial disease diagnosis by an oscillometric blood pressure device in primary care: validation and diagnostic accuracy study

Abstract: ObjectivesTo determine the level of agreement between a ‘conventional’ Ankle-Brachial Index (ABI) measurement (using Doppler and mercury sphygmomanometer taken by a research nurse) and a ‘pragmatic’ ABI measure (using an oscillometric device taken by a practice nurse) in primary care. To ascertain the utility of a pragmatic ABI measure for the diagnosis of peripheral arterial disease (PAD) in primary care.DesignCross-sectional validation and diagnostic accuracy study. Descriptive analyses were used to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 29 publications
1
14
1
Order By: Relevance
“…[14] The oscillometric measurement of ABI had a good correlation with Doppler ultrasound measurements, and there was little difference between the two different machines tested. [15161718] Our results are in contrast to a previous study in which the oscillometric method compared to the Doppler method showed that it was of low sensitivity (50%), specificity (100%), Kappa (0.65), and correlations in ABIs were 0.46 for the left leg and 0.61 for the right leg. [19] Some studies have shown that automatic oscillometric ABI devices (BOSO ABI) cannot be used interchangeably for standard Doppler ABI measurement in diagnosing PAD, but their high negative predictive value allows their use as a screening tool for PAD.…”
Section: Discussioncontrasting
confidence: 99%
“…[14] The oscillometric measurement of ABI had a good correlation with Doppler ultrasound measurements, and there was little difference between the two different machines tested. [15161718] Our results are in contrast to a previous study in which the oscillometric method compared to the Doppler method showed that it was of low sensitivity (50%), specificity (100%), Kappa (0.65), and correlations in ABIs were 0.46 for the left leg and 0.61 for the right leg. [19] Some studies have shown that automatic oscillometric ABI devices (BOSO ABI) cannot be used interchangeably for standard Doppler ABI measurement in diagnosing PAD, but their high negative predictive value allows their use as a screening tool for PAD.…”
Section: Discussioncontrasting
confidence: 99%
“…Eight studies included populations from Primary care services (mostly patients without symptoms of PAD), eight studies included populations from intermediate cardiovascular risk services and five studies included populations from Vascular services (mostly patients with symptoms of PAD). Weighted prevalence of PAD was 6.0% for Primary care, 25.5% for intermediate cardiovascular risk and 35.0% for Vascular services.…”
Section: Resultsmentioning
confidence: 99%
“…After exclusions, 1538 subjects (11 studies) and 3695 legs (11 studies) were analysed. Reasons for such exclusions were: (i) limb calcification, 16,17,[29][30][31][32][33][34] (ii) oscillometric errors 14,31,33,[35][36][37][38][39] and (iii) not all participants had their limbs measured using both the oscillometric and the Doppler. 40 In two studies, 16,17 a double analysis ("per subjects" and "per legs") was performed.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…The Heinz Nixdorf RECALL is also applying this method with the same 1.0 ABI cut-off (11). For the purpose of a primary care setting and use in a cardiovascular prevention program, the oscillometric method is simple, less time consuming, and cheap (22 25). Moreover, the variability of this device was lower compared to Doppler when applied in multicenter studies (25).…”
Section: Discussionmentioning
confidence: 99%